Potential force of infection of human rabies transmitted by vampire bats in the Amazonian region of Brazil - Schneider, Maria Cristina; Santos-Burgoa, Carlos; Aron, Joan; Munoz, Beatriz; Ruiz-Velazco, Silvia; Uieda, Wilson [UNESP] (American Society of Tropical Medicine and Hygiene, 1996)
Human rabies transmitted by bats has acquired greater epidemiologic relevance in various Latin American countries, just when cases transmitted by dogs have decreased. Concern has been heightened by reports of increased rates of bats biting humans in villages in the Amazonian region of Brazil. The aim of the present work was to estimate the potential force of infection (per capita rate at which susceptible individuals acquire infection) of human rabies transmitted by the common vampire bat if the rabies virus were to be introduced to a colony of bats close to a village with a high rate of human bites. The potential force of infection could be then used to anticipate the size of a rabies outbreak in control programs. We present an estimator of potential incidence, adapted from models for malaria. To obtain some of the parameters for the equation, a cross sectional survey was conducted in Mina Nova, a village of gold prospectors in the Amazonian region of Brazil with high rates of bates biting humans. Bats were captured near dwellings and sent to The Rabies Diagnostic Laboratory at the Center for Control of Zoonoses (Sao Paulo, Brazil) to be examined. To estimate the force of infection, a hypothetical rabies outbreak among bats was simulated using the actual data obtained in the study area. Of 129 people interviewed, 23.33% had been attacked by a vampire bat during the year prior to the study, with an average of 2.8 bites per attacked person. Males (29.41%) were attacked more often than females (11.36%); also, adults (29.35%) were attacked more often than children (8.33%). None of the 12 bats captured in Mina Nova tested positive for rabies, but the force of infection for a hypothetical outbreak was estimated to be 0.0096 per person per year. This risk represents 0.96 cases per 100 area residents, giving an incidence of 1.54 cases of bat-transmitted human rabies per year in the village of Mina Nova (160 inhabitants). The estimated risk is comparable with what has been observed in similar Brazilian villages.